Analisis Pendapatan Usahatani Jagung Hibrida Di Desa Lomuli Kecamatan Tiloan Kabupaten Buol - Wibawa, I Gede Laksana; Afrianto, Afrianto; Nugroho, Muhammad Fawzul Alif (Musamus University, 2024)
Farmers often borrow capital from middlemen in the form of production inputs such as seeds, fertilizer, and pesticides. The harvest must also be sold to the middleman who provides capital without an agreement on the selling price during harvest between the corn owner and the capital owner. This causes the tendency for the selling price of corn to be controlled by the middleman. The objective of this study is to see how much income Lomuli Village makes by growing hybrid corn. The determination of the research area was carried out purposively, namely in Lomuli Village, Tiloan District, Buol Regency. The technique employed to identify the sample was the simple random sampling method with 32 respondents. The data analysis method was carried out by analyzing corn farming income. Identification of expenses for farming activities carried out starting from production facilities to harvest. The income analysis used shows that hybrid corn farmers earn an income of IDR 11,256,193 per planting season for 1.45 ha of land, or IDR 7,802,337 per ha.